SINTOMAS DEPRESSIVOS EM MULHERES PROFISSIONAIS DO SEXO - Dell'Agnolo, Cátia Millene; Belentani, Leda Maria; Costa, Jaquilene Barreto da; Carvalho, Maria Dalva de Barros; Pelloso, Sandra Marisa (Revista Baiana de Enfermagem‏, 2014)